Uses and Perceptions of Music in Times of COVID-19: A Spanish Population Survey - Cabedo-Mas, Alberto; Arriaga-Sanz, Cristina; Moliner-Miravet, Lidon (Frontiers in Psychology, 2021)
Since March 14, 2020, Spanish citizens have been confined to their homes due to the impact of the COVID-19 pandemic. Participating in musical activities has been associated with reduced anxiety and increased subjective wellbeing. The aim of this study is to analyse how Spanish citizens used music during the lockdown period. We also study perceptions of the impact music has in everyday life, in particular examining the respondents’ insights into the effects of listening to music in situations of isolation. The study was conducted using the MUSIVID19 questionnaire administered to a total of 1868 Spanish citizens. The results indicate that during lockdown, respondents perceived an increase in the time they devoted to musical activities such as listening, singing, dancing or playing an instrument. The participants also reported using music to cope with the lockdown, finding that it helped them to relax, escape, raise their mood or keep them company. The findings suggest an improvement in their perception of the value of music in personal and social wellbeing during the lockdown. However, the study reveals significant differences in the use and perceptions of music according to respondents’ personal situations. Age and feelings of vulnerability may lead to more conservative uses of musical practice and to more moderate perceptions of the positive values of music.